Advances in physical ergonomics and safety - Ahram, Tareq Z.; Karwowski, Waldemar , 1953- (Advances in human factors and ergonomics series, 2013)
"Based on recent research, this book discusses physical ergonomics, which is concerned with human anatomical, anthropometric, physiological and biomechanical characteristics as they relate to physical activity. Topics include working postures, materials handling, repetitive movements, work-related musculoskeletal disorders, workplace layout, safety, and health" -- Provided by publisher